Molecular investigation of endoparasites of marine mammals (Cetacea: Mysticeti, Odontoceti) in the Western Mediterranean - Specht, Nicolas R.; Keve, Gergő; Fernández-Maldonado, Carolina; Caro, Alejandra Cerezo; Takács, Nóra; Kontschán, Jenő; Hornok, Sándor (Frontiers in Veterinary Science, 2024)
Whales, dolphins, and porpoises are susceptible to infections with protozoan and metazoan parasites. In this study, tissue samples, as well as flatworms and roundworms were collected from a common bottlenose dolphin (Tursiops truncatus), three short-beaked common dolphins (Delphinus delphis), two striped dolphins (Stenella coeruleoalba), a harbour porpoise (Phocoena phocoena), a long-finned pilot whale (Globicephala melas) and a fin whale (Balaenoptera physalus). These samples were molecularly analyzed. In one D. delphis, Toxoplasma gondii was detected in multiple organs, including the cerebellum. The cysts of the tapeworm Clistobothrium delphini and Clistobothrium grimaldii were identified in G. melas. Flukes collected from a D. delphis belong to Brachycladium atlanticum, while those removed S. coeruleoalba probably represent a new species. Four species of lungworms were also identified: Halocercus delphini in S. coeruleoalba, Halocercus sp. in T. truncatus, Stenurus globicephalae in G. melas, and a potentially new Pharurus sp. in P.phocoena.These findings show to the best of our knowledge for the first time, the presence of T. gondii DNA in D. delphis. The cerebellum of the animal was Toxoplasma-infected, which might be relevant to inadvertent stranding. In this study, new genetic markers were sequenced for several helminth parasites of marine mammals, possibly including undescribed species.